1990
DOI: 10.1159/000247924
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Patients with Anticentromere Antibody

Abstract: As has previously been reported by many investigators the anticentromere antibody is considered to be a useful serologic marker for the CREST (calcinosis, Raynaud’s phenomenon, esophageal involvement, sclerodactyly and telangiectasia) variant of systemic sclerosis. However, this antibody also appears in other conditions. By screening antinuclear antibody tests using HEp-2 cells as substrate, 39 patients were shown to have the anticentromere antibody. These patients were divided into 4 groups: group 1 = 17 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
(14 reference statements)
1
7
0
1
Order By: Relevance
“…Kallcnberget al [21] reported that ANA was detected in 62% of patients with RP, and the fre quency of positive ANA correlated with the number of organs affected and the severity of RP; ANA was present in 28% of patients without systemic involvement, whereas 75% of patients with organ involvement had positive ANA. More importantly, the presence of specific ANA such as ACA and anti-Scl-70 antibody has been shown to be a strong prognostic indicator for evolution into scleroderma disorders, as reported by our group and other investigators [13,16]. In the present study, we found that 56% of patients with RP had positive ANA, and most had positive specific ANA such as ACA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Kallcnberget al [21] reported that ANA was detected in 62% of patients with RP, and the fre quency of positive ANA correlated with the number of organs affected and the severity of RP; ANA was present in 28% of patients without systemic involvement, whereas 75% of patients with organ involvement had positive ANA. More importantly, the presence of specific ANA such as ACA and anti-Scl-70 antibody has been shown to be a strong prognostic indicator for evolution into scleroderma disorders, as reported by our group and other investigators [13,16]. In the present study, we found that 56% of patients with RP had positive ANA, and most had positive specific ANA such as ACA.…”
Section: Discussionsupporting
confidence: 86%
“…We have previously reported that patients with only RP and positive ACA at the first evaluation had developed skin sclerosis by the time of the follow-up evaluation more than 5 years later [16]. We therefore consider that patients with RP and ACA have a much higher chance of developing scle roderma and should be considered to belong to the scle roderma spectrum disorder group.…”
Section: Discussionmentioning
confidence: 96%
“…P-proteins (phosphorylated ribosomal proteins) are generally present in multiple copies on the ribosome and have isoelectric points in the range of 3 to 5, in contrast to most ribosomal proteins which are single copy and basic. A typical profile of an anti-ribosomal P-protein antibody specificity is composed of 3 antigens of 37kD (protein PO), 18kD (protein PI) and 15kD (protein P2) [92]. An additional band of approximately 20kD is often present as well.…”
Section: Ro (Ss-a) and La (Ss-b)mentioning
confidence: 99%
“…Clofazimine enhances the phagocytic and antimicrobial activity of human neutrophils and macrophages, by increasing lysosomic enzyme levels [ 1). This drug has also immunosuppressor and anti-inflammatory properties.…”
mentioning
confidence: 99%
“…In a recent issue of Dermalologica, Takehara et al [1] have pub lished a longitudinal study about patients with anticcntromcre antibody (ACA). They showed that cases with the simultaneous presence of ACA and Raynaud's phenomenon tend to exhibit the clinical signs of systemic sclerosis during the disease course [1|.…”
mentioning
confidence: 99%